Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1136/vr.105.12.267
|View full text |Cite
|
Sign up to set email alerts
|

Bovine leucosis (lymphosarcoma): a clinical study of 60 pathologically confirmed cases

Abstract: The clinical features of 60 pathologically confirmed cases of bovine leucosis (lymphosarcoma) are described. The majority of cases could be classified into one of four distinct clinical forms, ie, juvenile multicentric, thymic, skin and adult multicentric. Diagnosis of leucosis in animals with these forms was possible on clinical grounds alone. Five animals, four of which were adult, could not be thus classified and diagnosis required haematological and, or, pathological examinations. The clinical, epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…2 A clinical study of 60 pathologically confirmed cases of bovine lymphosarcoma was published in 1979, but these cases were mostly (78%) the calf multicentric and juvenile thymic forms. 3 A large retrospective study over 4 years on carcass condemnation rates for malignant lymphosarcoma in cattle in 2 abattoirs was conducted in California. However, this paper did not go into detail on the signalment, clinical signs, or organs affected.…”
mentioning
confidence: 99%
“…2 A clinical study of 60 pathologically confirmed cases of bovine lymphosarcoma was published in 1979, but these cases were mostly (78%) the calf multicentric and juvenile thymic forms. 3 A large retrospective study over 4 years on carcass condemnation rates for malignant lymphosarcoma in cattle in 2 abattoirs was conducted in California. However, this paper did not go into detail on the signalment, clinical signs, or organs affected.…”
mentioning
confidence: 99%
“…Manifestações clínicas que demonstram alterações no sistema respiratório (dispneia, taquipneia e estertoração pulmonar) foram observadas em aproximadamente um terço dos bovinos acometidos por linfoma neste estudo. Estas alterações estão diretamente relacionadas com aumento de linfonodos que envolvem o trato respiratório principalmente os mediastínicos, submandibulares e traqueobrôn-quicos (Marshak et al 1962, Grimshaw et al 1979, Ivany et al 2000, Barros 2007, Radostits et al 2007, Garry 2008. Além dos linfonodos, houve acometimento pulmonar em alguns casos, contribuindo para o agravamento dos sinais respiratórios.…”
Section: Discussionunclassified
“…3,4 In contrast, sporadic bovine lymphoma develops in young animals (often < 3 years old). 3,5 The calf form affects animals < 6 months old and results in lymph node enlargement with neoplastic infiltration of hematopoietic tissues in the bone marrow, liver, thymus, and spleen. 2 A genetic origin is also possible because familial thymic lymphoma has been reported.…”
Section: Commentsmentioning
confidence: 99%
“…2 A genetic origin is also possible because familial thymic lymphoma has been reported. 5 The thymic form affects bovids that are 6 months to 2 years old. 3,5 The calf form affects animals < 6 months old and results in lymph node enlargement with neoplastic infiltration of hematopoietic tissues in the bone marrow, liver, thymus, and spleen.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation